Inhibition of Pyroptosis of Renal Tubular Epithelial Cells by Puerarin via Regulation of lncRNA NEAT1 Ameliorating Chronic Renal Failure (Iranian Journal of Kidney Diseases, 2024)
Introduction. Chronic kidney disease (CKD) is one of the major chronic human diseases worldwide. Puerarin, extensively used in traditional Chinese medicine, has shown favorable clinical effects in treating CKD. Here, we aimed to elucidate the mechanism by which puerarin alleviates CKD. Methods. We constructed an animal model of CKD and intragastrically administered 400 mg/kg puerarin to the rat models. The extent of kidney injury was evaluated by performing hematoxylin and eosin staining. Then, we quantified the renal function indicators, inflammatory cytokines, apoptosis-related factors, and pyroptosis-related factors. HK-2 cells were treated with lipopolysaccharide (400 ng/mL) in H2O2 (200 μM) to induce oxidative stress. Then, the cells were treated with puerarin and transfected with overexpressed lncRNA NEAT1 vectors. Finally, the regulatory functions of lncRNA NEAT1 in cell apoptosis and pyroptosis were investigated. Results. Puerarin treatment alleviated kidney damage and suppressed inflammation and apoptosis in the CKD rat model. Puerarin ameliorated pyroptosis in the CKD model by inhibiting caspase-1 and GSDMD-N expression. LncRNA NEAT1 was down-regulated in the CKD model after puerarin treatment. Puerarin enhanced cell viability when lncRNA NEAT1 was overexpressed, and the inhibition of apoptosis was reversed in the LPS/H2O2-stimulated HK-2 cells. Furthermore, lncRNA NEAT1 overexpression blocked the anti-pyroptosis effect of Puerarin in the CKD model. Conclusion. Puerarin inhibits pyroptosis and inflammation by regulating lncRNA NEAT1, thereby ameliorating CKD.  DOI: 10.52547/ijkd.7565